A comparison between the impact of dynamic envelope control strategies on the buildings’ smart readiness indicator and modelled performance - Paydar, Meysam Akbari; Robertson, Craig; Burman, Esfandiar; Mumovic, Dejan (Building services engineering research & technology, 2025)
The Smart Readiness Indicator (SRI) was introduced in the revised EPBD (2018) to indicate how suitable a building is for smart operation. This study evaluates how varying functionality levels of dynamic envelope smart services, including movable shading control and window opening/closing control, impact the buildings’ SRI score and building performance. An office building located in London underwent both SRI assessment and performance simulation. Results revealed that changing the functionality levels of dynamic envelope services from the lowest to the highest resulted in only a 4.1% increase in the SRI score. Overall, the findings suggest a lack of significant correlation between the SRI score and the building’s projected performance. The variation in energy performance can be notably more pronounced than the alteration in the SRI score, or the adjustment in the SRI score may not necessarily induce a change in the building’s performance. Therefore, when undertaking the building design process, it is advisable to concurrently consider the SRI alongside the evaluation of building performance as well as the interaction between smart services and building design. This holistic approach is crucial for achieving an optimal design outcome. Practical application Significant efforts have been made to develop smart building assessment schemes, which can be highly beneficial in promoting the integration of smart services into buildings, and comparing the smartness levels of different buildings. Typically, these assessment schemes use a qualitative approach, evaluating buildings based on the presence of various smart services and their corresponding control strategies. However, to achieve optimal performance, it is essential to coordinate both building design and smart services by considering the building’s quantitative performance in addition to the qualitative assessment methods. This holistic approach enables a better understanding of the mutual impact between building design and smart services, facilitating well-informed decision-making.